2018
DOI: 10.4022/jafib.1798
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Myocardial Injury and Inflammation after Permanent Pacemaker Implantation: The Lead Fixation Type Effect

Abstract: cTnI and CRP can increase early after permanent pacemaker implantation, indicating mechanical myocardial injury and inflammation. The extent of these biomarkers elevation depends on the lead fixation type, and is not related to worse short-term prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Cardiac injury markers and systemic inflammatory markers have been reported to rise transiently after mechanical myocardial injury following cardiac device implantation. 15 We had performed AICD implantation once the cytokine levels had normalized and the patient was free of active COVID infection. However, the inflammatory markers and VPC burden showed a significant resurge following the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac injury markers and systemic inflammatory markers have been reported to rise transiently after mechanical myocardial injury following cardiac device implantation. 15 We had performed AICD implantation once the cytokine levels had normalized and the patient was free of active COVID infection. However, the inflammatory markers and VPC burden showed a significant resurge following the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that the mechanical effect of lead fixation on the myocardium may cause local injury, as evidenced by raised levels of plasma troponin and inflammatory biomarkers 1,2 . It is reported that transvenous insertion of the leads is followed by a sequence of cardiac histopathological changes, leading eventually to the formation of a fibrous connective tissue scar 3 . In the traditional way of pacing, most patients have a very slight troponin elevation after pacemaker implantation, leading to consider that it is not harmful to cardiac function and structure 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Ulinastatin has been proposed to serve as a myocardial protective agent, and it has been reported that ulinastatin improved the myocardial contractility, reduced the myocardial infarct size and decreased the levels of creatine kinase and cTnI in myocardial IR injury ( 16 ). cTnI is a highly sensitive and specific marker of myocardial injury ( 27 ). Mitochondria are important organelles for cardiomyocytes that not only provide the energy for cells, but can also trigger cell apoptosis ( 28 ).…”
Section: Discussionmentioning
confidence: 99%